P24 Vitamin D Levels Are Low In Sarcoidosis And Contribute To Abnormal Monocyte Activity. (10th November 2014) - Crawshaw, AP; Kendrik, YR; Estrada, F Martinez; Ho, L-P
Abstract : Introduction: Sarcoidosis is a multisystem inflammatory disorder. We showed recently that monocytes from patients with sarcoidosis exhibited reduced IL-10 production, and were less able to suppress T cell proliferation 1 . Vitamin D is reduced in a number of inflammatory and autoimmune disorders and has been shown to influence the activity of immune cells, including monocytes. We had observed reduced Vitamin D levels in our sarcoidosis patients and hypothesised that this may contribute to immune-pathology by altering monocyte function. Methods: Forty-six steroid-naïve, non-smoking individuals with histology-confirmed sarcoidosis were recruited from our Sarcoidosis-ILD service at first presentation. Serum calcidiol levels were compared with age and gender matched healthy controls. All donors were sampled between July and mid-October when Vitamin D levels were expected to be maximal. Monocytes were isolated using magnetic bead separation, stimulated with lipopolysaccharide (LPS) and cultured overnight with clinically 'sufficient' (10 –7 M) or 'deficient' (10 –8 M) levels of calcitriol. Monocyte function was assessed through cytokine production (by flow cytometry and ELISA) and multinucleate giant cell formation (MGC) ( in vitro fusion assay). Results: Vitamin D (calcidiol) levels were reduced in sarcoidosis (median 25.35 ng/ml [18.43–45.05]) compared with healthy controls (median 75.3 ng/ml [IQR 52.0–88.1]; p < 0.01). For the in vitro monocyte studies, calcitriol treatment resulted in adose-dependent (i) increase in monocyte IL-10 production ([IL-10-producing monocytes, as %total monocytes] from a baseline of10.2% [9.4–12.0] to 27.6% [25.6–29.4] when cultured with 'deficient' dose of vitamin D and to 30.8% [28.9–32.6]); p. Conclusions: Vitamin D levels are decreased in sarcoidosis patients at presentation. Monocyte IL-10 production was increased, and pro-TH1 differentiation cytokines were reduced with Vitamin D. Correcting Vitamin D deficiency in sarcoidosis patients may redress abnormal monocyte activity and reduce disease activity. Reference: Crawshaw A et al . Eur J Immunol. 2014